A process-based 222radon flux map for Europe and its comparison to long-term observations - Karstens, Ute; Schwingshackl, Clemens; Schmithüsen, Dominik; Levin, Ingeborg (Atmospheric chemistry and physics. Discussions, 2015)
Here we present a high-resolution 222Rn flux map for Europe, based on a parameterization of 222Rn production and transport in the soil. The 222Rn exhalation rate is parameterized based on soil properties, uranium content, and modelled soil moisture from two different land-surface reanalysis data sets. Spatial variations in exhalation rates are primarily determined by the uranium content of the soil, but also influenced by soil texture and local water-table depth. Temporal variations are related to soil moisture variations as the molecular diffusion in the unsaturated soil zone depends on available air-filled pore space. The implemented diffusion parameterization was tested against campaign-based 222Rn soil profile measurements. Monthly 222Rn exhalation rates from European soils were calculated with a nominal spatial resolution of 0.083° × 0.083° and compared to long-term direct measurements of 222Rn exhalation rates in different areas of Europe. The two realizations of the 222Rn flux map, based on the different soil moisture data sets, both realistically reproduce the observed seasonality in the fluxes but yield considerable differences for absolute flux values. The mean 222Rn flux from soils in Europe is estimated to be 10 mBq m−2 s−1 (ERA-Interim/Land soil moisture) or 15 mBq m−2 s−1 (GLDAS (Global Land Data Assimilation System) Noah soil moisture) for the period 2006-2010. The corresponding seasonal variations with low fluxes in winter and high fluxes in summer range in the two realizations from ca. 7 to ca. 14 mBq m−2 s−1 and from ca. 11 to ca. 20 mBq m−2 s−1, respectively. These systematic differences highlight the importance of realistic soil moisture data for a reliable estimation of 222Rn exhalation rates. Comparison with observations suggests that the flux estimates based on the GLDAS Noah soil moisture model on average better represent observed fluxes.
Im Titel ist die Zahl 222 hochgestellt
Gesehen am 12.06.2020